The Role of Agricultural Extension Worker and Babinsa TNI According to the Farmer's Perspective on The Implementation of Rice UPSUS Program in Gorontalo - Jaka Sumarno; Awaludin Hipi; Ari Widya Handayani; Ari Abdul Rouf (Jurnal Penyuluhan, 2019)
This study aims to analyze the role of Babinsa-TNI and field extension worker (PPL) assistance to the implementation of UPSUS programs and the success of UPSUS targets (increased production). The study was conducted at the UPSUS rice production center in Gorontalo Province, i.e; Bone Bolango District, Gorontalo Regency and North Gorontalo Regency. Sampling was done by simple random sampling method involving 162 respondent farmers during 2017. The measuring method to the role of Babinsa-TNI and field extension worker wasdone by Work Achievement Value Standard. The influence of Babinsa-TNI and field extension workerwas analyzed using the production analysis method usingproduction function of Cobb-Douglas stochastic frontier analysis. The results showed that the average Babinsa-TNI and field extension workerhad good performance in terms of high scoring value indicator. The Babinsa-TNI assistance in implementing the UPSUS program has a significant effect on increasing production and technical efficiency of rice production. The assistance of agricultural extension worker also has a positive effect on increasing production and technical efficiency of rice production.